Estimation of the Stability of Exotic Species of Dendroflora of Green Plantations of the Historical Part of Chernivtsi - Vanzar, Оksana; Romanyuk, Vasil (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The purpose of the research is to study the species composition, the present state and the stability of the main environmental factors of the exotic dendroflora of the parks of the historical part of Chernivtsi. The estimation of stability dendroflora exotic green spaces historical part of the city Chernivtsi. Based on taxonomic and biomorphological analysis of the current state of the dendroflora of the parks of the historical part of Chernivtsi, it has been established that 38 species of exotic species, consisting of 31 genera and 18 families, are growing in their territory. 10 species belong to the Pinophytha phylum and 28 species to Magnoliophytha. When assessing the stability of exotic species of dendroflora of green plantations of the historical part of Chernivtsi to atmospheric pollutants, pests and diseases, the predominance of exclusively gas-resistant species (19 species, 53%), exclusively resistant species to pests and diseases (26 species, 68%) and exclusively winter-resistant (33 species, 86%) plants. It was established that the species composition of the exotic species of the investigated dendroflora is fully adapted to the climatic conditions of the region and ensures the high success of the functioning of the green plantations of Chernivtsi.